Sustainable Entrepreneurial Empowerment For Indonesian Migrant Workers In Thailand: A Hybrid Community Mentoring Approach - Fatwa Zuhaena; Tri Esti Masita; Junivio Felix Da Silva Araujo; Dina Safitri; Anteng Febriana (CITAKARYA Jurnal Pengabdian Masyarakat, 2026)
Entrepreneurial preparedness has become increasingly important for Indonesian migrant workers as part of sustainable post-employment economic adaptation. Many migrant workers experience uncertainty regarding future economic opportunities after completing overseas employment due to limited entrepreneurial knowledge, business readiness, and sustainable mentoring access. This community service program aimed to strengthen entrepreneurial awareness and adaptive economic resilience among Indonesian migrant workers in Thailand through a hybrid community mentoring approach integrating online and onsite empowerment activities. The program involved Indonesian migrant workers participating in preliminary online counseling, onsite participatory mentoring, and post-program virtual evaluation sessions conducted between March and May 2026. A participatory empowerment approach was applied through collaborative mentoring, reflective discussion, entrepreneurial counseling, and sustainable monitoring activities. The findings demonstrated increased participant awareness regarding entrepreneurship, small-business opportunities, adaptive financial planning, and long-term economic sustainability. Participants also showed stronger motivation to develop future entrepreneurial initiatives after returning to Indonesia. Furthermore, the hybrid mentoring model facilitated continuous interaction and participatory engagement despite geographical limitations. This program contributes to the development of sustainable migrant empowerment practices through an adaptive hybrid entrepreneurial mentoring framework integrating digital communication and collaborative social engagement.